Prevalence of distal renal tubular acidosis in primary Sjögren's syndrome. (29th October 2014) - Both, Tim; Hoorn, Ewout J.; Zietse, Robert; van Laar, Jan A. M.; Dalm, Virgil A. S. H.; Brkic, Zana; Versnel, Marjan A.; van Hagen, P. Martin; van Daele, Paul L. A.
Abstract : Objectives. Our objectives were to analyse the prevalence of distal renal tubular acidosis (dRTA) in primary SS (pSS) and to compare a novel urinary acidification test with furosemide and fludrocortisone (FF) with the gold standard ammonium chloride (NH4 Cl) to detect dRTA. Methods. Urinary acidification was assessed in 57 pSS patients using NH4 Cl and FF. A urinary acidification defect was defined as an inability to reach a urinary pH of <5.3 after NH4 Cl. Results. The prevalence of complete dRTA (urinary acidification defect with acidosis) was 5% (3/57). All three patients had positive SSA/Ro and SSB/La autoantibodies and impaired kidney function. The prevalence of incomplete dRTA (urinary acidification defect without acidosis) was 25% (14/57). Compared with patients without dRTA, patients with incomplete dRTA had significantly lower venous pH and serum bicarbonate and higher urinary pH. SSB/La antibodies were more prevalent in the dRTA groups ( P < 0.05). Compared with NH4 Cl, the positive and negative predictive values of FF were 46% and 82%, respectively. Vomiting occurred more often during the urinary acidification test with NH4 Cl than with FF (9 vs 0, P < 0.05). Conclusion. Incomplete dRTA is common in pSS and causes mild acidaemia and higher urinary pH, which may contribute to bone demineralization and kidney stone formation. FF cannot replace NH4 Cl in testing urinary acidification in pSS, but may be considered as a screening tool, given its reasonable negative predictive value and better tolerability.